Control of bancroftian filariasis in the Pacific - Kessel, John F. (1962)
Although the etiological agent and the vector of filariasis were recognized early in the history of tropical medicine, control programmes were slow in developing, mainly because efficient filaricides were not known. Following the discovery of diethylcarbamazine, however, control projects were inaugurated in many parts of the world, including a number among island populations of the Pacific, in ideal conditions for observation and assessment. This paper reviews the answers to questionnaires sent to twelve areas in the Pacific where control projects have been undertaken. The most rapid and effective results appear to have been obtained in the Society Islands and Niue and Atiue, where mass treatment of the whole population with diethylcarbamazine was employed simultaneously with mosquito control. The authors conclude from the answers received that most control projects support the combined use of diethylcarbamazine and mosquito control, and that, where a control programme has brought the microfilaraemia rate down to 5% or less, the launching of an eradication programme should be considered.